Group Exhibition-The Right to Silence? International Group Exhibition - Antoniou, Klitsa (My University, 2026)
The Right to Silence? International Group Exhibition Curated by Sozita Goudouna (invited curator) & Thalia Vrachopoulos (Jonh Jay Faculty) Anya and Andrew Shiva Gallery, Jonh Jay, New York New York, USA, 2020